THE IMPLEMENTATION OF GENERATIVE TEACHING MODEL TO IMPROVE LEARNING STUDENTS’ ACHIEVEMENT OF THE STUDENTS VIII B5 CLASS OF INFORMATION AND COMMUNICATIONS TECHNOLOGY (ICT) AT SMP NEGERI 6 SINGARAJA - Ni Putu Hermi Witari Lastri (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
This study was aimed at (1) improving learning students’ achievement of VIII B5 class at SMP Negeri 6 Singaraja in 2011-2012 of Information and Communications Technology (ICT) in order to apply of the Generative Teaching Model; (2) knowing the students respond of VIII B5 class to apply the Generative Teaching Model of Information and Communications Technology (ICT). This study is a classroom action research design that used in 2 cycles by involving a total number of  30 students of VIII B5 class at SMP Negeri 6 Singaraja second semester in 2011/2012. The object of this research were learning students’ achievement and students response in basic competency of making simple number processing document of Information and Communications Technology (ICT). The learning students’ achievement data was collected based on cognitive test, psychomotor observation and affective observation. Meanwhile, the students’ response data was collected by using questionnaire. The obtained data were analyzed descriptively.  The result of the study showed that (1) there was improvement of learning students’ achievement of VIII B5 class at II cycle to apply the Generative Teaching Model of Information and Communications Technology (ICT). The results indicated that the learning students’ achievement score include: there was improvement of averaging class about 5,92 is 75,73 at I cycle become 81, 65 for II cycle. There was improvement of digestibility about 5,29% is 75,73 of I cycle and 81, 65% for II cycle. Meanwhile, there was improvement of classical completeness learning students from 66,67% at I cycle become 100% at cycle II by improving about 33,33%, (2) The students’ responses towards Generative Teaching Model of Information and Communication Technology (ICT) by averaging about 48,43. The results indicated that the implementation of Generative Teaching Model could successfully improve the learning students’ achievement of Information and Communications Technology.